하수 중 N-nitrosodimethylamine 분포 및 라니티딘에 의한 이의 형성: 클로라민 처리 방법과 산화 전처리 영향 - 민기; 손아섬; 조강우; 홍석원 (대한상하수도학회, 2022)
N-nitrosodimethylamine (NDMA) is a potent carcinogen that frequently detects nitrosamine from water chloramination. This study investigated the occurrence of NDMA and its potential precursor, ranitidine (RNT), in four wastewater treatment plants (WWTPs). Additionally, the effects of chloramination methods and oxidative pretreatment on the NDMA formation potential (FP) were assessed. Concentration levels of NDMA in the WWTPs waters ranged from 2.5 (detection limit) to 72.6 ng/L, while RNT values ranged from 1.32 to 186.9 ng/L. Further study indicated that the NDMA-FPs from chloraminated wastewaters varied between 36.2 and 227.8 ng/L. Nonetheless, chloramination methods and oxidative pretreatment significantly impacted the NDMA-FP levels. For example, breakpoint chlorination and stepwise chloramination promoted NDMA-FP when compared to preformed chloramination, which could be attributed to the formation of dichloramine and chlorine species. In contrast, prechlorination was found to effectively mitigate NDMA-FP, based on integrated ultraviolet (UV) irradiation. Notably, UV irradiation with free chlorine (UV/Cl2) or permanganate (UV/MnO4 -) reduced NDMA-FP by up to 70%. This study suggests that UV/MnO4 - and UV/Cl2 may be used as alternative mitigation strategies for reducing nitrosamine-FP in the water treatment process.